Annika. Season two [videorecording (DVD)] - Walker, Nick, 1969- (PBS Distribution, 2023)
Detective Inspector Annika Strandhed and the Marine Homicide Unit return to solve more brutal and unexplained murders that wash up in Scotland's waters. The team is challenged as their dynamics shift, pushing them to rapidly adapt as they encounter murders more complex than ever before.